Influence of a polyurethane diacrylate and hexanediol diacrylate ratio on the photocrosslinking and properties of UV-cured coatings - Hien, Le Xuan; Hung, Dao Phi (Vietnam Journal of Science and Technology, 2019)
Influence of a polyurethane dicarylate (UDA) and hexanediol diacrylate (HDDA) ratio on the photocrosslinking and properties of the systems based on UDA, HDDA and photoinitiator I.184 has been investigated. It was demonstrated that in the range of the UDA/HDDA ratio from 80/20 to 20/80, the fine, smooth films were obtained when the ratios were from 60/40 to 40/60 and the lower UDA/HDDA ratio, the faster conversion of acrylate groups. The acrylate groups in the investigated coatings were converted rapidly, leading to formation of tridimensional polymer networks and change of physico-mechanical properties of the coatings.